Immunogenicity of anti-TNFα therapy in psoriasis: a clinical issue?. (December 2013) - De Simone, Clara; Amerio, Paolo; Amoruso, Giuseppe; Bardazzi, Federico; Campanati, Anna; Conti, Andrea; Gisondi, Paolo; Gualdi, Giulio; Guarneri, Claudio; Leoni, Luca; Loconsole, Francesco; Mazzotta, Annamaria; et al.
Abstract : Introduction: Immunogenicity of antitumor necrosis factor-alpha (TNFα) agents has been proven to play a significant role in the variability of clinical responses among patients with chronic inflammatory diseases. However, its clinical impact on the outcome of patients with psoriasis and psoriatic arthritis receiving anti-TNFα treatment is not yet fully clear. Despite the high rates of efficacy of anti-TNFα agents in psoriasis, a substantial proportion of patients remain who experience a primary or secondary failure or significant side effects, which are potentially ascribable to immunogenicity. Areas covered: Topics include immunologic response elicited by anti-TNFα agents, the impact of immunogenicity on treatment response to anti-TNFα and the role played by immunogenicity in the lack of efficacy of anti-TNFα agents (infliximab, adalimumab and etanercept) in psoriasis. Expert opinion: Based on data available in the literature and the clinical experience of the authors, this article suggests the optimal approach to drug monitoring and antidrug antibody assay and the most effective use of biologic immunotherapies in this setting. Immunogenicity should be taken into account in the adoption of therapeutic choices in psoriatic patients, such as anti-TNFα agent intensification, or switching to another anti-TNFα agent or a drug with a different mechanism of action.